Analysis of Storage Lipid Accumulation in Alcanivorax borkumensis: Evidence for Alternative Triacylglycerol Biosynthesis Routes in Bacteria - Kalscheuer, Rainer (American Society for Microbiology, 2007)
Marine hydrocarbonoclastic bacteria, like Alcanivorax borkumensis, play a globally important role in bioremediation of petroleum oil contamination in marine ecosystems. Accumulation of storage lipids, serving as endogenous carbon and energy sources during starvation periods, might be a potential adaptation mechanism for coping with nutrient limitation, which is a frequent stress factor challenging those bacteria in their natural marine habitats. Here we report on the analysis of storage lipid biosynthesis in A. borkumensis strain SK2. Triacylglycerols (TAGs) and wax esters (WEs), but not poly(hydroxyalkanoic acids), are the principal storage lipids present in this and other hydrocarbonoclastic bacterial species. Although so far assumed to be a characteristic restricted to gram-positive actinomycetes, substantial accumulation of TAGs corresponding to a fatty acid content of more than 23% of the cellular dry weight is the first characteristic of large-scale de novo TAG biosynthesis in a gram-negative bacterium. The acyltransferase AtfA1 (ABO_2742) exhibiting wax ester synthase/acyl-coenzyme A:diacylglycerol acyltransferase (WS/DGAT) activity plays a key role in both TAG and WE biosynthesis, whereas AtfA2 (ABO_1804) was dispensable for storage lipid formation. However, reduced but still substantial residual TAG levels in atfA1 and atfA2 knockout mutants compellingly indicate the existence of a yet unknown WS/DGAT-independent alternative TAG biosynthesis route. Storage lipids of A. borkumensis were enriched in saturated fatty acids and accumulated as insoluble intracytoplasmic inclusions exhibiting great structural variety. Storage lipid accumulation provided only a slight growth advantage during short-term starvation periods but was not required for maintaining viability and long-term persistence during extended starvation phases.